1998
DOI: 10.1038/sj.bmt.1701336
|View full text |Cite|
|
Sign up to set email alerts
|

Acute graft-versus-host disease after bone marrow transplantation with a single HLA-DPB1*1001 mismatch: involvement of different TCRBV subsets

Abstract: Summary:HLA-DP incompatibility is not considered as an exclusion criterion for bone marrow donors, because such incompatibility was not shown to affect significantly the risk for acute graft-versus-host disease (GVHD). In line with this clinical observation, it was proposed that in the context of bone marrow transplantation, HLA-DP determinants did not function as transplantation antigens in the same way as HLA-A, -B or -DR. In contrast to the above conclusion, we recently demonstrated the presence of HLA-DPB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…[13][14][15][16][17][18] HLA-DP-specific T-cells have been isolated from skin biopsies at the onset of graft-versushost-disease (GvHD) in HLA-DP mismatched transplants. 19 It has also been reported that most leukaemic blasts are accessible to direct lysis by allogeneic HLA-DPspecific T cells, suggesting that these cells may also be responsible for an antileukaemic effect. 20 Although it was previously reported that DPB1 had no impact on the incidence of transplant complications, such as acute GvHD, (aGvHD), 21,22 there has since emerged evidence that HLA-DPB1 does play a role in alloreactivity following HSCT.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18] HLA-DP-specific T-cells have been isolated from skin biopsies at the onset of graft-versushost-disease (GvHD) in HLA-DP mismatched transplants. 19 It has also been reported that most leukaemic blasts are accessible to direct lysis by allogeneic HLA-DPspecific T cells, suggesting that these cells may also be responsible for an antileukaemic effect. 20 Although it was previously reported that DPB1 had no impact on the incidence of transplant complications, such as acute GvHD, (aGvHD), 21,22 there has since emerged evidence that HLA-DPB1 does play a role in alloreactivity following HSCT.…”
mentioning
confidence: 99%
“…In transplant setting allogeneic HLA-DP-specific T cells have been identified in both GVHD and GVL cases. [6][7][8][9] However, the importance of this locus, as a transplantation antigen remained poorly understood. One of the reasons that this antigen has received less attention is the weak linkage disequilibrium, dependent on a recombination hot spot between the HLA-DQ and DP loci.…”
Section: Discussionmentioning
confidence: 99%
“…The HLA-DPB1*1001-specific T cell clone CTLVB2 was derived from the skin biopsy of a patient with acute GVHD after an allogeneic BMT. 20 The B lymphoblastoid cell lines used …”
Section: T Cell Clones and B Cell Linesmentioning
confidence: 99%
“…Although increased risk of GVHD due to HLA-DPB1 incompatibility is not statistically detectable, 15,16 HLA-DP-specific T cells can be isolated from skin biopsies at the onset of GVHD each time an HLA-DP mismatch is present. [17][18][19][20] If an HLA-DP mismatch can induce an allogeneic response in vivo, it should be able to trigger both a GVH and a GVL effect (as long as leukemic cells express HLA-DP antigens). We are currently considering the use of HLA-DPB1-specific T cell clones transfected with the viral HSv-tk gene and directed against an HLA-DPB1 mismatch allele in the GVH direction (to spare regenerating hematopoiesis) in order to generate an allogeneic GVH-GVL effect in the context of a T cell-depleted BMT.…”
mentioning
confidence: 99%